2015
DOI: 10.1001/jamaneurol.2014.3442
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinfectious Diseases

Abstract: Despite significant advancements in the management of infectious diseases, central nervous system (CNS) infections remain a major challenge. They are often difficult to diagnose, and treatments are inadequate or nonexistent. Not surprisingly, encephalitis has been the subject of several recent movies and of fiction and nonfiction books, and outbreaks have received wide attention by the popular media. For example, bovine spongiform encephalopathy (mad cow disease) continues to get wide media coverage despite th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Immunocompromised patients present particular challenges because they are susceptible to unusual neuroinvasive pathogens that might not be part of a neurologist’s standard diagnostic algorithm 2 , 10 , 17 , 23 – 26 . In addition, many emerging and re-emerging pathogens have neuroinvasive potential, including Ebola, measles, mumps, Nipah, Hendra, Chikungunya, Zika and Powassan viruses 4 , 23 , 24 , 27 29 . Zika virus had been circulating in Brazil for 18 months before it was identified and for 24 months before it was determined that it was responsible for a spike in cases of microcephaly and Guillain–Barré syndrome 30 .…”
Section: Metagenomics For Neurological Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunocompromised patients present particular challenges because they are susceptible to unusual neuroinvasive pathogens that might not be part of a neurologist’s standard diagnostic algorithm 2 , 10 , 17 , 23 – 26 . In addition, many emerging and re-emerging pathogens have neuroinvasive potential, including Ebola, measles, mumps, Nipah, Hendra, Chikungunya, Zika and Powassan viruses 4 , 23 , 24 , 27 29 . Zika virus had been circulating in Brazil for 18 months before it was identified and for 24 months before it was determined that it was responsible for a spike in cases of microcephaly and Guillain–Barré syndrome 30 .…”
Section: Metagenomics For Neurological Infectionsmentioning
confidence: 99%
“…Indeed, many epidemiological studies have shown that an aetiological diagnosis is not obtained in ~50% of patients with encephalitis 2 , 3 . Improved diagnostic testing modalities are urgently needed to enhance individual patient care and to expand our understanding of the full spectrum of clinical phenotypes with which neurological infections can manifest 4 .…”
Section: Introductionmentioning
confidence: 99%
“…2 Fueled by globalization and climate change, we will continue to experience a changing landscape of neurological infections. The technologies described earlier have already affected improved diagnosis of novel and unusual pathogens, and may eventually lead to dramatic new therapies.…”
Section: Discussionmentioning
confidence: 99%
“…2 This commentary highlights 2 important “next-generation” approaches to diagnosis and therapy that are either already clinically relevant or likely to be tested in central nervous system (CNS) neurotropic viral infections in the near future.…”
mentioning
confidence: 99%
“…Concern is growing about novel neurologic infections 6 , due to the emergence of new pathogens, the spread of existing pathogens to new regions as a consequence of globalization, climate change, increased virulence of existing pathogens and increasing numbers of immunocompromised patients [7][8][9] . This is particularly true for Southeast Asia, a focal point for zoonotic and vector-borne diseases emergence 10,11 .…”
mentioning
confidence: 99%